Experimental and Numerical Investigation of Fuel-Lean H2/CO/Air and H2/CH4/Air Catalytic Microreactors. Issue 2 (1st February 2018) - Sui, Ran; Es-sebbar, Et-touhami; Mantzaras, John; Prasianakis, Nikolaos I.
ABSTRACT: The catalytic combustion of fuel-lean H2 /CO/air and H2 /CH4 /air mixtures (equivalence ratios φ = 0.3–0.5) was investigated experimentally and numerically in a 30 × 30 × 4 mm 3 microreactor made of SiC and equipped with six 1.5-mm internal diameter platinum tubes. The goal was to demonstrate high surface temperatures (>1200 K) with good spatial uniformity, for power generation applications in conjunction with thermophotovoltaic devices. Surface temperatures were measured with an infrared camera while exhaust gas compositions were assessed with a micro gas chromatograph. Three-dimensional simulations with detailed hetero-/homogeneous chemistry, conjugate heat transfer in the solid, and external heat losses complemented the measurements. The diverse transport (Lewis number), kinetic (catalytic reactivity), and thermodynamic (volumetric heat release rate) properties of the H2, CO, and CH4 fuels gave rise to rich combustion phenomena. Optimization of the channel flow directions mitigated the high spatial non-uniformities of temperature, which were induced by the low Lewis number of H2 . Measured surface temperature distributions had mean values as high as 1261 K, with standard deviations as low as 10.6 K. Syngas or biogas (H2 /CO mixtures) yielded lower wall temperatures compared to undiluted H2, even for small volumetric CO:H2 ratios (1:9 and 2:8). Although CO had a high catalytic reactivity when combusting in H2 /CO mixtures, its larger than unity Lewis number did not allow for the attainment of high surface temperatures. Mixtures of H2 /CH4 (such as fuels produced by natural gas decarbonization) were the least attractive due to the substantially lower catalytic reactivity of CH4 .